ナンキョクヨウ ニオケル カイリュウ ト セイヘン ジュンカン テンリュウ - 熊凝, 武晴; クマゴリ, タケハル; KUMAGORI, Takeharu (国立極地研究所, 1963)
P(論文) Of the surface ocean currents in the Antarctic seas, there are found the eastward-flowing current running east in the water Lat. 50°-60°S and the westward-flowing current more or less circling Antarctica in the water. South of Lat. 60°S, the latter being drifted by east wind. The first Antarctic expedition by the UMITAKA-MARU in 1957 discovered a recurvature current occurring in the water south of Lat. 60°-65°S between these two currents, as the result of differential speed of east-drifting wind and the eastward-flowing current, and the recurvature current flowing in the direction, southeast, south, southwest, southeast. The present survey confirmed the existence of this current through the observation conducted in the water of Long. 80°E-Long. 20°W. departmental bulletin paper